Effect of EVA, CFROI, MVA and CVA Methods on Shareholders Value Maximization and Financial Performance Estimation: An Empirical Study - Yaman, Kemal; Topal, Seda (Journal of Applied And Theoretical Social Sciences, 2024)
With the globalization of markets, competition and performance pressure have accelerated. Investors rightfully expect a reasonable return on the capital they make available to others. Since companies often achieve their growth through capital obtained from new shareholders, the pressure on company profitability increases significantly. The capital market rewards companies' good performance and also punishes their bad performance. At this point, Economic Value Added (EVA), Cash Flow Return on Investment (CFROI), Cash Value Added (CVA) and Market Value Added (MVA), which ensure value maximization, have become increasingly important problems. For this reason, company profitability and growth potential are important. Within the scope of this study, the importance of EVA, CFROI, CVA and MVA indicators and their comparison with traditional methods are discussed in the introduction part. Studies on these indicators that embody value maximization are examined through a literature review. In the methodology section, the data of 11 companies active in the healthcare sector listed on Borsa Istanbul are analyzed through regression and correlation analyzes on the basis of the 2015-2021 period, and the effects of these indicators on stock returns. As a result, when MVA, CVA, CFROI and EVA are positive, economic profit is achieved and shareholder value is expected to increase.